Implementing computer‐mediated intercultural communication in English education: A critical reflection on its pedagogical challenges - Lee, K. (Journal of computer assisted learning, 2018)
Integrating computer‐mediated intercultural communication (CMIC) activities into language curricula has been discussed as an innovative approach. Despite the increasing number of successful examples reporting positive outcomes of adopting CMIC activities in language‐learning environments, it has also been noted that there are significant pedagogical challenges observed when CMIC activities are introduced into classrooms. However, previous studies tend only to briefly mention some of those challenges and to list general solutions to them, rather than deeply engaging with the issues and their educational and social consequences upon students' learning practices. Thus, this qualitative case study documents diverse pedagogical challenges faced by Korean students and teacher in their English‐as‐a‐foreign language classroom, in which a series of CMIC activities were set up and conducted. The challenges analysed in this paper include the unrealistically high implementation cost, the educational inequality issues created by irreducible gaps in students' socio‐economic backgrounds, and the unresolved struggles to develop positive student subjectivities and linguistic identities. In conclusion, the article proposes three instructional principles, drawn in turn from the two closely interrelated theories: multiliteracies pedagogy and critical pedagogy. Fundamentally, the author argues that effective adoption of CMIC activities needs a more pedagogically, socially, and culturally sensitive approach. Lay Description What is currently known about the subject matter: Computer‐mediated intercultural communication (CMIC) has been integrated in language curricular. The CMIC facilitates the development of students' intercultural communicative competence. Its implementation has been perceived successful in enhancing English‐as‐a‐foreign language students learning attitudes and outcomes. What their paper adds to this: However, its implementation process can be very costly and time‐/resource‐consuming. There seem to be also subtle but negative educational and social consequences observed. There are some serious inequality issues created by irreducible gaps in students' cultural capitals. The implications of study findings for practitioners: Three teaching principles to address those challenges and issues are proposed. The effective adoption of the CMIC needs a more pedagogically, socially, and culturally sensitive approach. It contributes to developing the sensitive approach.